2011
DOI: 10.1016/j.biomaterials.2010.09.033
|View full text |Cite
|
Sign up to set email alerts
|

The surface immobilization of the neural adhesion molecule L1 on neural probes and its effect on neuronal density and gliosis at the probe/tissue interface

Abstract: Brain tissue inflammatory responses, including neuronal loss and gliosis at the neural electrode/tissue interface, limit the recording stability and longevity of neural probes. The neural adhesion molecule L1 specifically promotes neurite outgrowth and neuronal survival. In this study, we covalently immobilized L1 on the surface of silicon based neural probes and compared the tissue response between L1 modified and non-modified probes implanted in the rat cortex after 1, 4, and 8 weeks. The effect of L1 on neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 52 publications
8
130
1
Order By: Relevance
“…As the PDMS carrier accounts for the major part of the implant surface, neuronal processes may tend to migrate away from the cochlear implant. The recent work by Cui et al [42,43] sheds a light on the important role of the substrate on the biocompatibility of neural probes. In these studies, neuronal loss and gliotic response within the vicinity of unmodified neural probes implanted into the CNS were significantly reduced by surface immobilisation of neuron specific L1 protein on the substrate of the neural probes [42,43].…”
Section: In Vitro Growth and Differentiation Of Pc12mentioning
confidence: 98%
See 1 more Smart Citation
“…As the PDMS carrier accounts for the major part of the implant surface, neuronal processes may tend to migrate away from the cochlear implant. The recent work by Cui et al [42,43] sheds a light on the important role of the substrate on the biocompatibility of neural probes. In these studies, neuronal loss and gliotic response within the vicinity of unmodified neural probes implanted into the CNS were significantly reduced by surface immobilisation of neuron specific L1 protein on the substrate of the neural probes [42,43].…”
Section: In Vitro Growth and Differentiation Of Pc12mentioning
confidence: 98%
“…The recent work by Cui et al [42,43] sheds a light on the important role of the substrate on the biocompatibility of neural probes. In these studies, neuronal loss and gliotic response within the vicinity of unmodified neural probes implanted into the CNS were significantly reduced by surface immobilisation of neuron specific L1 protein on the substrate of the neural probes [42,43]. A comprehensive approach, combining both electrode and substrate modification, may lead to a better solution to a stable and long-term implant-neural interface [44].…”
Section: In Vitro Growth and Differentiation Of Pc12mentioning
confidence: 98%
“…These observations were further corroborated in vivo, wherein L1 coated silicon probes implanted in the rat cortex demonstrated significantly increased axonal density, and reduced glial scarring both acutely (1 week) and chronically (4 and 8 weeks) postimplantation. 124 Overall, these studies demonstrate that while ECM coatings can be used effectively to promote cell attachment and differentiation, informed strategies, such as the use of L1 protein coated probes, can help promote neuron specific attachment and outgrowth, and help mitigate reactive gliosis around chronically implanted neuroprostheses.…”
Section: Intracortical Neural Interface Recording Functionmentioning
confidence: 98%
“…Improvements in chronic neural interfacing and chronic recording function have also been studied in vivo using neural adhesion molecule L1 immobilized interfaces. 123,124 Previous in vitro studies have demonstrated the successful attachment, change in morphology, and proliferation of E9 chicken cortical neurons on silicon wafers coated with collagen-1, polylysine, and laminin. 94 Since laminin alone adhered poorly, these surfaces were initially coated with polylysine and followed by laminin coating to increase adsorption.…”
Section: Intracortical Neural Interface Recording Functionmentioning
confidence: 99%
“…151,[160][161][162][163] Molecular strategies include using neurotrophic factors and/or modulated drug-delivery to reduce the foreign body response. [164][165][166] In order for intracortical electrodes to become a viable clinical BCI option where patients may need to use the device for decades, the robustness and longevity of recordings needs to be improved. Drawbacks of ECoG and intracortical BCIs include required implantation surgery, cost, and increased system complexity.…”
Section: Ecog and Intracortical Microelectrode Bcismentioning
confidence: 99%